The WRKY Transcription Factor WRKY71/EXB1 Controls Shoot Branching by Transcriptionally Regulating RAX Genes in Arabidopsis. Issue 11 (17th November 2015) - Guo, Dongshu; Zhang, Jinzhe; Wang, Xinlei; Han, Xiang; Wei, Baoye; Wang, Jianqiao; Li, Boxun; Yu, Hao; Huang, Qingpei; Gu, Hongya; Qu, Li-Jia; Qin, Genji
Abstract : EXB1 plays pivotal roles in shoot branching by positively regulating the key branch genes RAX1, RAX2, and RAX3 and by affecting auxin pathways. Abstract: Plant shoot branching is pivotal for developmental plasticity and crop yield. The formation of branch meristems is regulated by several key transcription factors including REGULATOR OF AXILLARY MERISTEMS1 (RAX1), RAX2, and RAX3. However, the regulatory network of shoot branching is still largely unknown. Here, we report the identification of EXCESSIVE BRANCHES1 (EXB1), which affects axillary meristem (AM ) initiation and bud activity. Overexpression of EXB1 in the gain-of-function mutant exb1-D leads to severe bushy and dwarf phenotypes, which result from excessive AM initiation and elevated bud activities. EXB1 encodes the WRKY transcription factor WRKY71, which has demonstrated transactivation activities. Disruption of WRKY71/EXB1 by chimeric repressor silencing technology leads to fewer branches, indicating that EXB1 plays important roles in the control of shoot branching. We demonstrate that EXB1 controls AM initiation by positively regulating the transcription of RAX1, RAX2, and RAX3 . Disruption of the RAX genes partially rescues the branching phenotype caused by EXB1 overexpression. We further show that EXB1 also regulates auxin homeostasis in control of shoot branching. Our data demonstrate that EXB1 plays pivotal roles in shoot branching by regulating both transcription of RAX genes and auxin pathways.